Hypermethylation of UCHL1 Promotes Metastasis of Nasopharyngeal Carcinoma by Suppressing Degradation of Cortactin (CTTN) - Yin Zhao; Yuan Lei; Shi-Wei He; Ying-Qin Li; Ya-Qin Wang; Xiao-Hong Hong; Ye-Lin Liang; Jun-Yan Li; Yang Chen; Wei-Jie Luo; Pan-Pan Zhang; Xiao-Jing Yang; et al. (Cells, 2020)
Epigenetic regulation plays an important role in the development and progression of nasopharyngeal carcinoma (NPC), but the epigenetic mechanisms underlying NPC metastasis remain poorly understood. Here, we demonstrate that hypermethylation of the UCHL1 promoter leads to its downregulation in NPC. Restoration of UCHL1 inhibited the migration and invasion of NPC cells in vitro and in vivo, and knockdown of UCHL1 promoted NPC cell migration and invasion in vitro and in vivo. Importantly, we found that UCHL1 interacts with CTTN, and may function as a ligase promoting CTTN degradation by increasing K48-linked ubiquitination of CTTN. Additionally, restoration of CTTN in NPC cells that overexpressed UCHL1 rescued UCHL1 suppressive effects on NPC cell migration and invasion, which indicated that CTTN is a functional target of UCHL1 in NPC. Our findings revealed that UCHL1 acts as a tumor suppressor gene in NPC and thus provided a novel therapeutic target for NPC treatment.